Digital technologies in shaping the image of the political elite of Saint Petersburg - Alexandra S. Merkusheva; Ekaterina A. Tuzova; Nikita V. Grishanin (RUDN Journal of Public Administration)
Analyzing the modern trend of “digitalization” in various spheres of contemporary social life, the authors considered its applications in order to form the image of the political elite of Saint Petersburg in the person of representatives of the legislative power of the city - the deputies of the Legislative Assembly of Saint Petersburg. This analysis is important for the construction of competent and relevant communication with the public, as well as in the formation of the trend for openness and transparency of communication between the authorities and the population. Moreover, the authors explore how digital tools and platforms can enhance civic engagement and participation, providing a framework for understanding the dynamics of power and accountability in the digital age. The findings underscore the necessity for political representatives to adapt to technological advancements to foster trust and collaboration with constituents, ultimately contributing to a more informed and engaged society.